Crab-Aquatic Plant System: A Model for Taking Ecological and Economical Care of the Lakes in Yellow River Delta, China - Zhiguo, Liu; Wei, Gao; Wen , Chang; Jinming, Liu (The Global Environmental Engineers, 2023)
The lakes, including reservoirs and ponds in the Yellow River Delta, are characterized by many fragile ecosystems and low economic values. How to take into account both ecology restoration and the economic benefits of the lakes in this region is a complex problem. The Chinese mitten crab (Eriocheir sinensis)-aquatic plant system may have this potential. In this study, we planted aquatic plants, e.g., Elodea nuttallii, Hydrilla verticillate, and Vallisneria natans, with the crabs and investigated geochemical parameters in the ponds. The concentration of NH4+-N was lower than 0.5 mg/L, the pH of the breeding peiponds was 8.274-9.365, and the dissolved oxygen was 3.554-6.048mg/L, which was better than the class II environmental quality standards for surface water. The more extensive specifications ( > 150g/pcs) of the crab growth with the aquatic plants account for >35% of the total production. This model is significant to the ecological utilization of reservoirs in the Yellow River Delta but has low promotion. Therefore, some compulsory breeding policies and breeding standards must be proposed. It is the current ecological needs of the ecological protection Yellow River Delta.